comparison of the combination of recomline and ELISA with real- time polymerase chain reaction on the final diagnosis of toxoplasmosis - ALfakhar, Suha A.; Guirges, Sami Y.; ALkhafaji, Jassim T.; jabir, Maysoon M. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: The diagnosis of Toxoplasma gondii infection in human can be determined by variable immunological and molecular methods.